Potential Therapeutic Targeting Neurotransmitter Receptors in Diabetes - Pan, Xiaohui; Tao, Shibing; Tong, Nanwei (Frontiers in Endocrinology, 2022)
Neurotransmitters are signaling molecules secreted by neurons to coordinate communication and proper function among different sections in the central neural system (CNS) by binding with different receptors. Some neurotransmitters as well as their receptors are found in pancreatic islets and are involved in the regulation of glucose homeostasis. Neurotransmitters can act with their receptors in pancreatic islets to stimulate or inhibit the secretion of insulin (β cell), glucagon (α cell) or somatostatin (δ cell). Neurotransmitter receptors are either G-protein coupled receptors or ligand-gated channels, their effects on blood glucose are mainly decided by the number and location of them in islets. Dysfunction of neurotransmitters receptors in islets is involved in the development of β cell dysfunction and type 2 diabetes (T2D).Therapies targeting different transmitter systems have great potential in the prevention and treatment of T2D and other metabolic diseases.